Ergonomics in surgery and work-related musculoskeletal disorders - Külekçioğlu, Sevinç; Dilektaşlı, Evren; Kömürcü, Erkam; Kuytu, Turgut; Uçak, Hande (The European Research Journal, 2025)
Objectives: Our study aimed to determine surgeons' work-related musculoskeletal disorders, physical workload, location of the disorder, frequency, characteristics, and effects on daily life. Furthermore, we aimed to draw attention to ergonomics education by investigating surgeons' opinions and attitudes regarding ergonomics. Methods: Data were collected using survey forms from 37 surgeons who met the appropriate criteria. Sociodemographic characteristics, The Physical Workload Questionnaire was used to evaluate physical workload, the Extended Nordic Musculoskeletal System Questionnaire was used to evaluate the characteristics of painful areas, and the Beck Depression Scale was used to evaluate the psychological status of the surgeons. Results: Thirty-four (91.9%) of the surgeons reported that they experienced musculoskeletal disorders at least once in their careers due to their professional responsibilities. The most common causes of pain were poor posture, incorrect positioning, and standing too much. The neck, upper back, and waist were the most affected areas, and only 1 (2.7%) surgeon had received ergonomics training. Conclusions: Musculoskeletal disorders caused by ergonomic difficulties are common in the surgical field. It is critical to developing evidence-based ergonomic training recommendations that hospitals and residency training programs should follow to protect surgeons from preventable injuries that have the potential to significantly harm their careers.